SERUM HSP 70 LEVELS OF CHRONIC HEPATITIS B PATIENTS ARE SUBSTANTIALLY CORRELATED WITH HBsAg - Awaz Saadi (Euromediterranean Biomedical Journal, 2020)
Heat-shock protein 70 (HSP70) is a stress-induced protein that demonstrates the anti-apoptosis response that ensures the survival of cells. The aim of this study is to investigate the significant correlation of serum HSP70 levels in chronic hepatitis B viral infection (HBV) patients. The study was performed on fifty-three chronic HBV patients from June–December 2015. HBV-DNA, HBsAg, HBeAg, and anti HBeAb, ALT, AST, ALP, and AFP levels were determined. Serum HSP70 level was estimated for positive HBV patients. The results showed a significant correlation between HSP70 [mean of 41.325±29.7206], HBsAg [mean of 12074.93±5681.619] at p=0.006 [P=or <0.01], and also between HBV DNA [3.2E+10±2.4E+11] and HBeAg [96454.29321±300533.25] at P=0.002 [P= or <0.05]. The expression of HSP70 is increased significantly with the increase of HBsAg titre, which together may work as indicators of chronic HBV infection.